The effect of playing electronic games on student behavior in public schools in Jordan from the teachers’ point of view - AlRiahneh, Nabhan Housni Turaikhim (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the effect of playing electronic games on students’ behavior in public schools in Jordan from the teachers’ point of view, and to achieve the aim of the study, the corresponding study tool was prepared and its validity and reliability were confirmed. The study sample consisted of a number of public school teachers in the Northern Jordan Valley. In the governorate of Irbid, who numbered (45) teachers, and they were chosen by the intentional method, the researcher used the qualitative approach to suit the nature of the study and its objectives, and the study reached the following results: The results of the interviews of the respondents showed that there are unusual behaviors that appeared on students as a result of their merging with electronic games and this What all the interviewed individuals indicated, and the majority of the study sample indicated that there are changes in students ’behavior such as irritation, violence, hitting, blind imitation of some wrong behaviors, immoral habits and negative habits that affected their social habits with their peers, and most of the respondents indicated that the academic achievement of students who Playing electronic games has clearly decreased, and in light of the results of the study, the researcher presented many m The recommendations include conducting many studies and research on the impact of electronic games at different age stages, educating parents about the danger of electronic games on children, holding awareness and introducing workshops on the dangers and negatives of electronic games, highlighting the school’s role in addressing the problem of electronic games for students, by educating them and guiding them about the harms of this Games for their behaviors.